A method for calculating gear meshing efficiency by measured data from gear test machine. (April 2018) - Wang, Cheng; Wang, Shou-ren; Wang, Gao-qi
Highlights: A calculation method for the experimental gear meshing efficiency is proposed. The formula of the experimental gear meshing efficiency is deduced. The approach is suitable for the power open and closed type gear test machine. Abstract: Gear meshing efficiency is an important component of gear transmission efficiency, and the meshing efficiency of gear is directly related to device performance and energy consumption. The gear meshing efficiency can't be obtained directly from the measurement results of gear test machine. It is rarely reported effective method to calculate the gear meshing efficiency with measured data from gear test machine, which limits the verification of theoretical calculation method of gear meshing efficiency. Therefore, a method for calculating gear meshing efficiency by measured data from gear test machine is proposed in the paper. It is suitable for power closed type gear test machine, and suitable for power open one as well. Firstly, according to the type of gear test machine, the corresponding calculation method of gear transmission efficiency is confirmed. Secondly, the gear transmission efficiency under both unloaded and loaded conditions, the total power under loaded conditions and friction-related losses at the bearings are calculated at a given speed, respectively. Finally, substituting the calculation results of friction-related losses at the bearings, total power under loaded conditions and the gear transmission efficiency both unloaded and loaded conditions into the gear meshing efficiency calculation formula, and gear meshing efficiency by measured data from gear test machine is obtained. An example is presented to verify the proposed method.